Solute hydrogen and deuterium observed at the near atomic scale in high-strength steel - Breen, Andrew J.; Stephenson, Leigh T.; Sun, Binhan; Li, Yujiao; Kasian, Olga; Raabe, Dierk; Herbig, Michael; Gault, Baptiste (Acta Materialia, 2020)
Observing solute hydrogen (H) in matter is a formidable challenge, yet, enabling quantitative imaging of H at the atomic-scale is critical to understand its deleterious influence on the mechanical strength of many metallic alloys that has resulted in many catastrophic failures of engineering parts and structures. Here, we report on the APT analysis of hydrogen (H) and deuterium (D) within the nanostructure of an ultra-high strength steel with high resistance to hydrogen embrittlement. Cold drawn, severely deformed pearlitic steel wires (Fe–0.98C–0.31Mn–0.20Si–0.20Cr–0.01Cu–0.006P–0.007S wt%, ε=3.1) contains cementite decomposed during the pre-deformation of the alloy and ferrite. We find H and D within the decomposed cementite, and at some interfaces with the surrounding ferrite. To ascertain the origin of the H/D signal obtained in APT, we explored a series of experimental workflows including cryogenic specimen preparation and cryogenic-vacuum transfer from the preparation into a state-of-the-art atom probe. Our study points to the critical role of the preparation, i.e. the possible saturation of H-trapping sites during electrochemical polishing, how these can be alleviated by the use of an outgassing treatment, cryogenic preparation and transfer prior to charging. Accommodation of large amounts of H in the under-stoichiometric carbide likely explains the resistance of pearlite against hydrogen embrittlement.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Atom probe tomography; Deuterium; Hydrogen embrittlement; Pearlitic steel